Analyzing the Spanish strip cipher by combining combinatorial and statistical methods. Issue 3 (3rd May 2016) - Sanguino, Luis Alberto Benthin; Leander, Gregor; Paar, Christof; Esslinger, Bernhard; Niebel, Ingo
ABSTRACT: According to historical reports, many telegrams that date from the Spanish Civil War (1936–1939) still remain undisclosed. It is believed that these telegrams were encrypted with a cryptosystem called the "Spanish Strip Cipher" (SSC). During this civil war, SSC was the most used cryptographic algorithm. This method corresponds to a homophonic substitution cipher in which a plaintext letter can map to between three and five ciphertext symbols. By means of cryptanalysis, the authors detect a weakness in the encryption process of the SSC. In this article, they describe how this vulnerability is exploited to efficiently reconstruct a plaintext from a relatively short ciphertext. The attack is based on combinatorial and statistical methods, and it is divided into three phases: homophones-table analysis, letter-frequency analysis, and dictionary search. The attack was implemented in Java and tested on a laptop with an i7 processor and 4 GB of RAM. The tests were carried out with several real telegrams from the Spanish Civil War. In this article, the authors provide the results of one test that was successfully performed only using the first 201 ciphertext symbols of a Spanish telegram.